An HST/STIS view of protoplanetary discs in Upper Scorpius: observations of three young M stars. Issue 2 (17th April 2021) - Walker, Sam; Millar-Blanchaer, Maxwell Andrew; Ren, Bin; Kalas, Paul; Carpenter, John
ABSTRACT: We present observations of three protoplanetary discs in visible scattered light around M-type stars in the Upper Scorpius OB association using the Space Telescope Imaging Spectrograph (STIS) instrument on the Hubble Space Telescope ( HST ). The discs around stars 2MASS J16090075–1908526, 2MASS J16142029–1906481, and 2MASS J16123916–1859284 have all been previously detected with the Atacama Large Millimeter/submillimeter Array (ALMA), and 2MASS J16123916–1859284 has never previously been imaged at scattered light wavelengths. We process our images using reference star differential imaging, comparing and contrasting three reduction techniques – classical subtraction, Karhunen–Loève Image Projection, and non-negative matrix factorization, selecting the classical method as the most reliable of the three for our observations. Of the three discs, two are tentatively detected (2MASS J16142029–1906481 and 2MASS J16123916–1859284), with the third going undetected. Our two detections are shown to be consistent when varying the reference star or reduction method used, and both detections exhibit structure out to projected distances of ≳200 au. Structures at these distances from the host star have never been previously detected at any wavelength for either disc, illustrating the utility of visible-wavelength observations in probing the distribution of small dust grains at large angular separations.